Effectiveness of Electrolyte Solution on Changes in Apples Fruit Quality - Putri, Diana Risa; Fauzi, Siska (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The process of discoloration is an indication of damage in food. In this case, apples are one of the commodities that often experience this event. The cause of the discoloration is the polyphenol oxidase (PPO) enzyme. One possible prevention that can be used to inhibit the discoloration event is by administering ascorbic acid, iodine, and glucose compounds. The purpose of this study was to analyze the color changes in apples after being treated with ascorbic acid, iodine, and glucose. Color change testing was carried out using immersion in the three solutions. The results obtained from this study were that the treatment of the three solutions for 6 hours, 12 hours, 24 hours, 36 hours, and 48 hours was able to inhibit the discoloration of the cut apples. Increasing the concentration of ascorbic acid, iodine, and glucose solutions causes an increase in the ability to inhibit the browning reaction. In addition to the concentration factors of the three solutions, soaking time also affects the quantity of color change inhibition.